Fabrication of Customized Sectional Impression Trays in Management of Patients with Limited Mouth Opening: A Simple and Unique Approach. (24th July 2013) - Krishna CH, Vamsi; Mahendranadh Reddy, K.; Gupta, Nidhi; Mahadev Shastry, Y.; Chandra Sekhar, N.; Aditya, Venkat; Reddy, G. V. K. Mohan
Abstract : Impression making is not only important but is also the most significant step in the fabrication of any fixed or removable prosthesis. Proper impression making may be hindered by certain pathologic conditions. Reduced mouth opening is one of the common mechanical obstructions for proper orientation of the impression tray in the patient's mouth. In patients with trismus induced by submucous fibrosis, the procedure may be even more difficult to carry out because of reduced tissue resiliency and obliteration of vestibular spaces. Use of sectional trays offers one of the alternatives to overcome the problem of restricted mouth opening. Fabrication of customized impression trays according to the patient dentition improves the accuracy of impression making. The present case reports describe the fabrication of sectional custom trays designed for dentulous patients with chronic tobacco-induced submucous fibrosis.